Pengaruh Kebisingan terhadap Resiko Terjadinya Gangguan Suara pada Karyawan Workshop Future Furniture di Colomadu - Noor Farahin, Arfiah; Purnaningrum, Windiarti Dwi (Politeknik Kesehatan Kemenkes Surakarta, 2023)
ABSTRACT Background: Advances in technology since the last three decades have led to an increase in the dangers of noise both in number, intensity, speed and number of people exposed to noise, especially in industrialized and developed countries. Continuous noise disturbance can have a negative impact on the condition of the surrounding environment, comfort, and the quality of one's health. Purpose: This study aims to determine whether there is an effect of noise on the risk of Sound Disorder among future furniture workshop employees in Colomadu. Method: his type of research is a quantitative research with the method used descriptive verification method. The number of samples in this study were 45 employees of the Colomadu future furniture workshop, who were selected using the total sampling technique. The statistical test used is the independent t-test. Research Result: On equal variance assumed, the t value is 3340 and the significance level is p = 0.02. This indicates that p <0.05, which means that there is an average difference in terms of noise level. So it can be concluded that there is an influence between the noise of the work environment and sound disorder at the Surakarta City Future Furniture Workshop. Conclusion: A person's voice will increase when talking accompanied by exposure to noise from environmental noise. Voice disorders are a negative result of voice formation that occurs in people who use their voices too loudly and for a long time. Keywords: Noise, Sound Disorder, VHI